Prevalence and Prognostic Impact of Hyponatremia in Patients with Acute Exacerbations of Chronic Obstructive Pulmonary Disease: A Retrospective Observational Study - George, Jofin; Kakodkar, Uday C; Talaulikar, Nikita S (National Journal of Medical Research, 2025)
Background: Few studies determine the prevalence and clinical progress of hospitalized patients having hyponatremia with COPD exacerbation. The objectives were to determine the prevalence of hyponatremia in hospitalized patients of COPD exacerbation, and compare the clinical and laboratory parameters in these patients. Methodology: Retrospective observational study was carried out among 200 patients admitted with COPD exacerbation over a period of three months from October to December 2024. Patients of CKD, CLD, acute cardiac events, hypernatremia and deaths were excluded. Hyponatremia was defined as serum sodium <136mmol/L. Poor progress was defined as prolonged stay (>8 days), or readmission within one month of previous hospitalization. Results: 112(56%) cases had hyponatremia (128.98±5.85 vs 138.88±2.22 mmol/L, 95%CI: t=16.45, p<0.001). Patients with hyponatremia were older (71.68±8.093 vs 68.8±7.645 years, 95%CI: t=2.562, p=0.011), had longer hospital stay (11.77±7.263 vs 7.24±2.849 days, 95%CI: t=6.035, p<0.001), lower albumin (95%CI: t=2.798, p=0.006), and a higher chance of being mechanically ventilated (OR=2.39, 95%CI: 1.34-4.22, p=0.003). Patients developing hospital acquired infection were more likely to develop hyponatremia (OR=18.9, 95%CI: 2.48-144, p<0.001). Hyponatraemic patients had poorer progress (OR=4.83, 95%CI: 2.64-8.84, p<0.001) and higher readmission rates (OR=6.07, 95%CI: 2.25-16.4, p<0.001). Conclusions: Patients of COPD exacerbation have high prevalence of hyponatremia which requires early detection, routine screening, and monitoring for clinical deterioration.